Levels of mercury and hydroquinone in some skin-lightening creams and their potential risk to the health of consumers in Ghana. - Amponsah, Doreen (2011)
A Thesis submitted to the Department of Chemistry, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Science